Apparent Comorbidity of Bipolar Disorder in a Population With Combat-Related Post-Traumatic Stress Disorder. Issue 2 (1st February 2014) - McLay, Robert N.; Ram, Vasudha; Webb-Murphy, Jennifer; Baird, Alicia; Hickey, Anita; Johnston, Scott
ABSTRACT: Combat is often associated with the diagnosis of post-traumatic stress disorder. Battle may also lead to other emotional extremes. Sometimes this is enough to meet criteria for a diagnosis of bipolar disorder (BPD), but it is open to debate if this is clinically appropriate. This study examined the rate of BPD, as assessed by structured interview, in combat veterans who clinicians believed met the criteria for post-traumatic stress disorder but not BPD. Structured interviews were conducted with 109 such participants. Close to 81% endorsed a history of a major depressive episode, 34.9% endorsed a history of manic episode, and 27.5% endorsed a history of a hypomanic episode. According to the interviews, 54.1% participants experienced BPD, including 34.9% who experienced BPD type I. Clinicians were aware of these results and observed the individuals for a prolonged period afterward, but the clinical diagnosis did not change to include BPD in any of these individuals. Future research is needed to establish reliable and valid methods to make a diagnosis of BPD in the presence of comorbid conditions and stressors and thus guide clinicians with better treatment options.